2021
DOI: 10.37319/iqnjm.3.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Covid-19 Vaccine Among General Population in Iraq

Abstract: COVID19 emerged as one of the biggest global public health crises in recent history. Many pharmaceutical companies have raced against time to develop a vaccine, so that the pandemic can be brought under control. The aim of the current study was to assess the acceptance of the COVID19 vaccine among the general population in Iraq. A cross-sectional study was conducted among 1069 respondents from different states of Iraq using questionnaires administered online. Though a total of 77.6% of the respondents agreed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Ghazi et al, studied the acceptance of the COVID-19 vaccine in Iraq, about half of the participants preferred AstraZeneca, while small proportions of the Iraqi populations preferred the Chinese vaccine, however, the Pfizer vaccine was not included in the study [16]. There was a significant association between vaccine type and prevalence of adverse effects with AstraZeneca and Pfizer having the highest rates of adverse effects in comparison to the Sinopharm vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Ghazi et al, studied the acceptance of the COVID-19 vaccine in Iraq, about half of the participants preferred AstraZeneca, while small proportions of the Iraqi populations preferred the Chinese vaccine, however, the Pfizer vaccine was not included in the study [16]. There was a significant association between vaccine type and prevalence of adverse effects with AstraZeneca and Pfizer having the highest rates of adverse effects in comparison to the Sinopharm vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have found that older respondents are more likely to accept vaccination (Al-Mohaithef and Padhi, 2020; Coe et al, 2022;Malik et al, 2020), while others have found no link (Harapan et al, 2020;Wang et al, 2020). According to the findings of Ghazi et al, (2021), respondents who accept vaccination are substantially younger. A possible explanation of the current study result is that nursing faculty members are considered specialists and are more committed to preventive measures.…”
Section: The Results Of the Studymentioning
confidence: 97%
“…In Hasanain study, 19 the Oxford (AstraZeneca) vaccination was favored by nearly half (48.6%). In Saied's study 14 among Egyptian health workers (46.2%) reported preferring Pfizer-BioNTech and in AL-Snaafi's study 12 preferred the Pfizer-BioNTech vaccine which is much higher than Al-Zahraa university students' preference for the same vaccine.…”
Section: Discussionmentioning
confidence: 98%